The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3748/wjg.14.3416
|View full text |Cite
|
Sign up to set email alerts
|

Treatment responses in Asians and Caucasians with chronic hepatitis C infection

Abstract: AIM:To conduct a multicentre retrospective review of virological response rates in Asians infected with genotype 1 chronic hepatitis C (CHC) treated with combination interferon and ribavirin and then to compare their responses to that among Caucasians. METHODS: Asian patients infected with genotype 1 CHC treated at 4 Australian centres between 2001 to 2005 were identified through hospital databases. Baseline demographic characteristics, biochemical, virological and histological data and details of treatment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…Moreover, Asian HCV patients had a higher frequency of the common homozygote. Therefore, as demonstrated in previous studies (45,46), Asian HCV patients had a better response to treatment than European patients in this study. Ge et al (12) found that the SVR rates across different population groups displayed a striking concordance with C allele frequency.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, Asian HCV patients had a higher frequency of the common homozygote. Therefore, as demonstrated in previous studies (45,46), Asian HCV patients had a better response to treatment than European patients in this study. Ge et al (12) found that the SVR rates across different population groups displayed a striking concordance with C allele frequency.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, it has also been well documented that East Asians have higher SVR rates than patients of European ancestry. 22,23 The SVR rates across different population groups displayed a striking concordance with C allele frequency which emphasizes the greater importance of individual genotype than ethnicity in predicting treatment response. 24 A previous study from Germany, extended to HCV genotype 2 and 3 infected patients, also analyzed 200 healthy controls for comparison and reported the frequency of CC, CT, and TT genotypes with 49%, 42.5%, and 8.5%, respectively.…”
Section: Genotyping Of Il28b Polymorphism (Rs12979860c/t)mentioning
confidence: 86%
“…Secondly, ethnicity has been shown to be a major predictive factor for uptaking treatment in previous studies, with AfricanAmericans and Hispanics less likely than Caucasians to commence on treatment [14,15]. Asian patients were shown to have different social demographics and different modes of acquisition [16]. They also have different views on doctors' role in their health.…”
Section: Discussionmentioning
confidence: 97%